Oral Health Status of elementary school aged children in Rawalpindi, Islamabad, Pakistan: Oral Health Status of Elementary School Aged Children - Farrukh Habib, Muhammad; Pervaiz, Ayesha; Shanzar Butt, Muhammad; Ali Khan, Asad; Muhammad Numan, Hafiz; Rafique, Rizwana (Pakistan Journal of Health Sciences, 2023)
Dental caries among Pakistani’s school children continue to increase. To identify treatment needs, current epidemiologic data are needed. Such statistics are currently not available for elementary school children. Objectives: To determine the oral status of school children using Decayed, Missed, Filled, Teeth index. To identify treatment need by using Community Periodontal Index of Treatment Needs index. Methods: An analytical cross-sectional study was performed on 385 elementary school children aged between 13 to 17 years. A simple random sampling method was performed. The participants were both from government and private schools of Rawalpindi, Islamabad, Pakistan. Data were collected by modified WHO questionnaire. Oral examinations were performed in accordance to WHO guidelines. After taking permission from school, informed consent from parents, and assent from students, oral examinations were done by undergraduate and DMFT and CPITN index were assessed. Results: Mean DMFT and CPITN score among school children came 1.17±2.182 and 1.04±0.910 respectively. More than a one-third of the elementary school students needed high level dental care. Conclusions: Oral health status of elementary school aged children is relatively unsatisfactory. There is a need to introduce dental camps and oral hygiene awareness programs in educational settings.